Financial Performance: Capital Structure, Debt Policy and Company Size in Manufacturing Companies Listed on the Indonesia Stock Exchange - Olandari Mulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to analyze the extent to which the capital structure, debt policy, and company size influence financial performance. This research employs a quantitative method with an ex-post facto approach. With the research data population there are 210 manufacturing companies listed on the Indonesian Stock Exchange per year, with 66 companies that meet the criteria each year using a purposive sampling technique. So the total samples obtained amounted to 330 company samples during the 2017-2020 period. Data were analyzed using SPSS version 25. The results of the analysis indicate that: (1) The capital structure variable (X1) -2.251 is smaller than the t-table value of 1.967267. With a significance level of 0.05 and a significance value of 0.025, Ho is rejected, and H1 is accepted. The first hypothesis is accepted. (2) The Debt Policy variable (X2) -3.499 is smaller than the t-table value of 1.967267. With a significance level of 0.05 and a significance value of 0.001, Ho is rejected, and H2 is accepted. The second hypothesis is accepted. (3) The firm size variable (X3) 4.417 is greater than the t-table value of 1.967267. With a significance level of 0.05 and a significance value of 0.000, Ho is rejected, and H3 is accepted. The third hypothesis is accepted. The results of statistical calculations show that F-count = 22.434 > F-table 2.63231 with a significance of 0.000 < 0.05, then Ho is rejected, and Ha is accepted. It can be concluded that there is a joint influence of the independent variables on the dependent variable.